Affirmative Action in Safeguarding Democracy: Revoking the Voting Rights of Civil Servants in Elections - Muhammad Faisal; Putriani Lumban Gaol; Syalwa Khairun Nisa; Yuliani Nasution (Eduvest - Journal of Universal Studies, 2025)
This article discusses the importance of maintaining the neutrality of the State Civil Apparatus (ASN) in elections and elections in Indonesia as well as the argument for abolishing ASN's right to vote as a form of affirmative action to maintain the integrity of democracy. Under Law No. 20 of 2023 on ASN, ASN has the right to vote as a citizen, yet neutrality violations are common, with many ASNs engaging in practical politics, either due to pressure from superiors or to advance personal careers. These violations undermine democratic principles that require elections to be conducted honestly, fairly, and without intimidation. In practice, sanctions against violations of ASN neutrality are still weak, which opens space for abuse of authority in politics. For this reason, the author proposes the elimination of ASN's right to vote as *affirmative action* to ensure the sustainability of democracy that is clean from political intervention. Although this elimination only has a small impact on the number of Permanent Voter Lists (DPT), it will improve the quality of Indonesian democracy by reducing the potential for manipulation by unscrupulous ASNs. In this context, the debate about the voting rights of non-TNI/Polri ASNs is irrelevant because all ASNs have the potential to violate neutrality. The author supports the discourse on the elimination of ASN's voting rights for the sake of creating elections with better quality and integrity.